Challenges and opportunity with big data : 19th Monterey Workshop 2016, Beijing, China, October 8-11, 2016, Revised selected papers /: 19th Monterey Workshop 2016, Beijing, China, October 8-11, 2016, Revised selected papers. (2017) - Unknown
No abstract available